2020
DOI: 10.5194/cp-2020-13
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Late Paleocene – early Eocene Arctic Ocean Sea Surface Temperatures; reassessing biomarker paleothermometry at Lomonosov Ridge

Abstract: Abstract. The Integrated Ocean Drilling Program Arctic Coring Expedition on Lomonosov Ridge, Arctic Ocean (IODP Expedition 302 in 2004) delivered the first Arctic Ocean sea surface temperature (SST) and land air temperature (LAT) records spanning the Paleocene-Eocene Thermal Maximum (PETM; ~56 Ma) to Eocene Thermal Maximum 2 (ETM2; ~54 Ma). The distribution of glycerol dialkyl glycerol tetraether (GDGT) lipids indicated elevated SST (ca. 23 to 27 °C) and LATs (ca. 17 to 25 °C). However, recent analytical devel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 106 publications
3
14
2
Order By: Relevance
“…The exact sources of these compounds in sedimentary archives and their temperature relation are as yet not fully understood. For example, brGMGTs in Paleogene Arctic Ocean sediments seem to be produced in a marine system with a strong oxygen minimum zone and substantial input of penecontemporaneous terrestrial matter (Sluijs et al, 2020). Similar to the temperature response of 5-methyl brGDGTs, the degree of methylation of acyclic brGMGTs (HMBT acyclic ) follows the TEX 86 in the Paleogene Arctic record.…”
Section: Advances In Gdgt Paleothermometrymentioning
confidence: 89%
See 3 more Smart Citations
“…The exact sources of these compounds in sedimentary archives and their temperature relation are as yet not fully understood. For example, brGMGTs in Paleogene Arctic Ocean sediments seem to be produced in a marine system with a strong oxygen minimum zone and substantial input of penecontemporaneous terrestrial matter (Sluijs et al, 2020). Similar to the temperature response of 5-methyl brGDGTs, the degree of methylation of acyclic brGMGTs (HMBT acyclic ) follows the TEX 86 in the Paleogene Arctic record.…”
Section: Advances In Gdgt Paleothermometrymentioning
confidence: 89%
“…Reconstructions of deep-sea (Westerhold et al, 2020) and sea surface temperature (Bijl et al, 2009(Bijl et al, , 2013aHollis et al, 2012Hollis et al, , 2019Frieling et al, 2014;Inglis et al, 2015;O'Brien et al, 2017;Evans et al, 2018;Cramwinckel et al, 2018;O'Connor et al, 2019;Sluijs et al, 2020) have revealed an overall cool climate in the Maastrichtian and Paleocene, long-term warming towards the early Eocene Climatic Optimum (EECO; 53.4-49.2 Ma) and subsequent cooling during the middle and late . The EECO stands out as particularly warm, with ice-free polar regions (Hollis et al, 2009(Hollis et al, , 2012Pross et al, 2012;Bijl et al, 2013a;Frieling et al, 2014;Hines et al, 2017).…”
Section: The Paleogene Southwest Pacific Oceanmentioning
confidence: 99%
See 2 more Smart Citations
“…This compilation also reveals lower SSTs near 50°N in the Callovo-Oxfordian. Russian Arctic SST are very close to Campanian-Maastrichtian and Early Eocene TEX86 H -derived SST (Jenkyns et al, 2004;Sluijs et al, 2020) and Early Eocene bioclimatic SST (Suan et al, 2017) from the Arctic (Fig. 5).…”
Section: Early Jurassic Latitudinal Temperature and δ 18 Ow Gradients 275mentioning
confidence: 62%